Patient involvement in questionnaire design: tackling response error and burden - Marissa Ayano Mes; Amy Hai Yan Chan; Vari Wileman; Caroline Brigitte Katzer; Melissa Goodbourn; Steven Towndrow; Stephanie Jane Caroline Taylor; Rob Horne (Taylor & Francis Group, 2019)
Questionnaires capture patient perspectives succinctly and at relatively low cost, making them a popular data collection tool for health researchers. However, questionnaire data can be affected by response error and response burden. Patient involvement during questionnaire design can help reduce the effect of response error and burden. This paper describes a novel approach for patient involvement during questionnaire design, combining methods from cognitive interviewing (Think Aloud Tasks) with an open-ended follow-up discussion to collate and act on patient feedback, while also taking account of the common challenges in questionnaire design (i.e. response error and burden). The strengths and limitations of this approach are discussed, and recommendations are made for future use.